Authorship diversity in Gastroenterology-related Cochrane systematic reviews: Inequities in global representation - Dhali, Arkadeep; D'Souza, Christopher; Rathna, Roger B.; Biswas, Jyotirmoy; Dhali, Gopal Krishna (Frontiers in Medicine, 2022)
The need for promoting diversity and equitable authorship representation in academics faces increasing recognition, with some articles pointing out the lack of diversity in specific fields. Currently, there are no such articles scrutinizing the author diversity in the field of Gastroenterology. Cochrane systematic reviews are perceived worldwide to be amongst the highest quality of evidence available, thereby its conclusions often impact policy and practice globally. However, little is known about the current state of authorship diversity in Gastroenterology-related Cochrane reviews.